The investigation of marek disease, lenfoid leucosis and reticuloendotheliosis by elisa and histopathologic methods in chickens in konya province - Uçkun Sait Uçan; Mehmet Ateş; M. Metin Kıran; H. Hüseyin Hadimli; Mustafa Ortatatlı; E. Özlem Kuyucuoğlu (Eurasian Journal of Veterinary Sciences)
There are three virus-caused neoplastic diseases with known etiology in poultry, Marek disease (MO). Lenfoid Leucosis (LL) and reticuloentdotheliosis (RE), Of these, MD is characterized by malign T cell transformation while LL comprises a variety of transmissible benign and malign neoplasms of different organs. RE is also characterized by lymphomas. The animal material of the study was determined by a questionaire work. A number of 540 blood/sera and 15 organ samples (liver, lien, kidney, bursa Fabricius, pancreas, lungs, glandular stomach and gizzard, Nervus ischiadicus, skin, brain and cerebellum) were collected from commercial and parent stock flocks located in the Konya Region. In this study, some epidemiological data were calculated following analysis of blood and serum samples by serological and histo pat ho logical techniques, There was statistically correlation between the histopathologic examination and ELISA (p<0,05). Anti-MHV antibodies were measured in 56 serum samples by ELISA. Only one serum sample was detected to show anti-LLV antibody. The epidemiological figures raised from this study were as follows: prevalance of the MD and LL were 10 % and 0.2 %, respectively. No findings were observed regarding RE infection in this study.